A facile synthesis of fluorescent silver nanoclusters with human ferritin as a synthetic and interfacing ligand1. Issue 10 (21st May 2015) - Lee, In Hwan; Ahn, Byungjun; Lee, Jeong Min; Lee, Chang Soo; Jung, Yongwon
<x xml:space="preserve">Abstract</x> Highly stable and copper-responsive fluorescent silver nanoclusters were assembled on human ferritin and retained the structure and function of the ferritin template as well as the fused binding protein.